The life and works of Robert Wood : classicist and traveller (1717-1771) - Finnegan Rachel; Mulvin Lynda (Archaeological lives., 2022)
The Life and Works of Robert Wood (1717-1771) commemorates the Irish classicist and traveller on the 250th anniversary of his death and provides the general reader with a source book for the fascinating life and career of a much-neglected figure in the realm of Irish eighteenth-century travels and antiquarianism.